The Role of Arabic In the Formation of Islamic Cultural and Scientific Identity - Prastika, Khalysta Geovanny; As Sya’bani, Muhammad Akmal Ubaidillah; Anshari, Muhammad Azmi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
In the formation of the identity of an Islamic Culture and Science in particular, we already know and understand that behind the formation there must be a very urgent role in it, one of which the researchers will discuss in this study is the Arabic Language. Where this article is researched aims to know and understand the extent of the urgency of Arabic in the formation and maintenance of a Cultural Identity and The Development Of Science In Islamic Civilization, because of its role, researchers are interested in studying the origin of the existence of Arabic on this earth. The method that will be used by researchers in this study is a method in the form of library research or what we commonly hear in a study, namely Library Research. Thus, the results of this study can be concluded that Arabic is not only a means of communication, but also has a strategic role in maintaining and developing Islamic Culture and Science. Therefore, efforts to strengthen the learning and mastery of Arabic are essential in maintaining The Sustainability Of Islamic Civilization, especially in the Era Of Globalization which is full of challenges.